1989
DOI: 10.1093/nar/17.12.4433
|View full text |Cite
|
Sign up to set email alerts
|

Differential repair of UV damage inSaccharomyces cerevisiae

Abstract: Preferential repair of UV-induced damage is a phenomenon by which mammalian cells might enhance their survival. This paper presents the first evidence that preferential repair occurs in the lower eukaryote Saccharomyces cerevisiae. Moreover an unique approach is reported to compare identical sequences present on the same chromosome and only differing in expression. We determined the removal of pyrimidine dimers from two identical alpha-mating type loci and we were able to show that the active MAT alpha locus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…The coupling of transcription to repair helps to prevent such a catastrophe. Such coupling, although not universal for all adducts (22) or all genes (23), has been documented in vivo in several systems (4)(5)(6)(7)23), and it also has been inferred from studies showing selective mutagenesis (24,25 Partial purification of a coupling factor that enhances repair oftemplate DNA when added to a defined transcription-repair system. The defined system consisted ofpDR3274 irradiated with 225 Jm-2 of UV as the template-substrate for purified RNA Pol, UvrA, UvrB, UvrC, UvrD, pol I, and DNA ligase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling of transcription to repair helps to prevent such a catastrophe. Such coupling, although not universal for all adducts (22) or all genes (23), has been documented in vivo in several systems (4)(5)(6)(7)23), and it also has been inferred from studies showing selective mutagenesis (24,25 Partial purification of a coupling factor that enhances repair oftemplate DNA when added to a defined transcription-repair system. The defined system consisted ofpDR3274 irradiated with 225 Jm-2 of UV as the template-substrate for purified RNA Pol, UvrA, UvrB, UvrC, UvrD, pol I, and DNA ligase.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently it was found that in both CHO and human cells, the template strand of the actively transcribed DHFR gene was repaired 2-to 10-fold more efficiently than the complementary strand, which was repaired at a rate comparable to that of nontranscribed regions (4). These observations, originally made in mammalian cells, have now been extended to other organisms including yeast (5,6) and Escherichia coli (7).…”
mentioning
confidence: 94%
“…MAT␣ and HML␣ fragments were generated by digesting genomic DNA with HaeII enzyme, which yields a 3.6-kb MAT␣ fragment and a 4.0-kb HML␣ fragment. The probe was an internal fragment of the Y␣ region of MAT␣, which is strictly ␣-specific (see below) (21). DNA (5 g) was restricted with HaeII and incubated at 37°C for 2 h. The DNA was recovered after phenol-chloroform extraction and resuspended in 10 l of denaturing loading buffer (12.5% Ficoll, 5 mM EDTA, 0.125% bromphenol blue, 0.25 M NaOH).…”
Section: Strains and Plasmids-the Radmentioning
confidence: 99%
“…Studies of repair in unique chromosomal DNA sequences did not show a strand bias in repair (7)(8)(9). In contrast, Smerdon and Thoma and colleague (10,11) reported that excision repair of CPDs in a plasmid was rapid for transcribed strands, while nontranscribed sequences were slowly repaired.…”
mentioning
confidence: 95%